The Orexin receptors: Structural and anti-tumoral properties - Couvineau, Alain; Nicole, Pascal; Gratio, Valérie; Voisin, Thierry (Frontiers in Endocrinology, 2022)
At the end of the 20th century, two new neuropeptides (Orexin-A/hypocretin-1 and Orexin-B/hypocretins-2) expressed in hypothalamus as a prepro-orexins precursor, were discovered. These two neuropeptides interacted with two G protein-coupled receptor isoforms named OX1R and OX2R. The orexins/OX receptors system play an important role in the central and peripheral nervous system where it controls wakefulness, addiction, reward seeking, stress, motivation, memory, energy homeostasis, food intake, blood pressure, hormone secretions, reproduction, gut motility and lipolysis. Orexins and their receptors are involved in pathologies including narcolepsy type I, neuro- and chronic inflammation, neurodegenerative diseases, metabolic syndrome, and cancers. Associated with these physiopathological roles, the extensive development of pharmacological molecules including OXR antagonists, has emerged in association with the determination of the structural properties of orexins and their receptors. Moreover, the identification of OX1R expression in digestive cancers encompassing colon, pancreas and liver cancers and its ability to trigger mitochondrial apoptosis in tumoral cells, indicate a new putative therapeutical action of orexins and paradoxically OXR antagonists. The present review focuses on structural and anti-tumoral aspects of orexins and their receptors.